Identification of Aircraft Parameters in the Lateral-Directional Flight Dimension with Variation of Control Input - Eries Bagita Jayanti; Fuad Surastyo Pranoto; Singgih Satrio Wibowo (National Institute of Aeronautics and Space - LAPAN, 2022)
In this research, the process of identifying aircraft parameters is carried out for the lateral-directional dimension by notice the variations of the given control surface deflection input. The inputs are pulse, doublet and 3-2-1-1. Among the input forms, it is not known which form is most suitable for the lateral-directional dimension. Simulation is done by varying the input deflection control surface and simulation time. The input given is deflection of the aileron and rudder control surfaces. This research uses the equation error method with the ordinary least square estimation technique. The purpose of this research to identify the most suitable input for the identification of parameters in the lateral-directional dimension and to observe the effect of simulation time. The aircraft used is the Lockheed C-5 Galaxy. The simulation results show that the combination of the 3-2-1-1 input form in the aileron deflection surface and the input pulse shape on the rudder has an error value of about 0.09. This value is smaller among all cases seen from the error matrix A. Based on that, the combination of the two inputs is the most suitable for the lateral-directional dimension than the other inputs that have been given.